Pengaruh Kepemimpinan Transformasional, Kompensasi Finansial dan Komunikasi Terhadap Kepuasan Kerja Karyawan Pada Legian Village Hotel Bali - Permata Sari, Anak Agung Mirah; Sriathi, Anak Agung Ayu (E-Jurnal Manajemen, 2014)
Job satisfaction is the perceived emotional state of employees about their jobs. This study focused on the Legian Village Hotel Bali with respondents 53 employees. Data analysis techniques are used to test the hypothesis that multiple linear regression analysis to determine the effect of F-test and t-test simultaneously to determine the effect of partial. Based on the results of analysis show that the variables of transformational leadership, financial compensation and simultaneous communication significant effect on employee job satisfaction at Legian Village Hotel Bali with a contribution of 38.5 percent. Variable transformational leadership, and communication of financial compensation is also positive and significant effect on employee job satisfaction partially on Legian Village Hotel Bali with financial compensation variable as the variable most dominant influence on employee job satisfaction. Keywords: transformational leadership , financial compensation, communication and job satisfaction
Keywords: transformational leadership; financial compensation; communication; job satisfaction